Sorte vinske trte v tradicionalnih vinogradih na slovenskem Štajerskem - Vršič, Stanko (University of Maribor Press, 2026)
Grapevine Varieties in Traditional Vineyards of Slovenian Styria. The heart of this work on ampelography naturally focuses on describing ("graphy") all the vines ("ampelos") of Slovenian Styria, carefully categorizing them according to their degree of historical diffusion or rarity, down to the precious native wild vines. Tthe result is of great use to a varied readership that includes winegrowers, students, nurserymen, oenologists, viticultural technicians, hybridizers, researchers, historians, and amateurs!